2021
DOI: 10.4143/crt.2020.1066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience of Male Primary Choriocarcinoma at the Samsung Medical Center

Abstract: PurposeThe objective of this study was to describe and analyze the clinicopathological features of primary choriocarcinoma (PCC) observed in male patients treated at the Samsung Medical Center between 1996 and 2020. Materials and MethodsWe reviewed the clinical records of 14 male patients with PCC retrospectively to assess their demographic, histological, and clinical characteristics at the time of diagnosis as well as identify the treatment outcomes. ResultsThe median age of the patients was 33 years. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Results from a previous SEER database study on extragonadal choriocarcinoma in males reported a median survival of 12 months and a 5-year CSS of 25% among 67 patients with mediastinal primary choriocarcinoma NOS or choriocarcinoma combined with other germ cell elements, which is the same to that obtained in our 87 patients of the same histologies 35. A small series of Korean patients from the Samsung Medical Center reported a median OS of 8 months for the group of 6 patients with primary mediastinal choriocarcinoma 36. Concerning mediastinal yolk sac tumors, the prognosis seems to be better than that of the rest of the NS tumors, as well as those obtained in our series.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Results from a previous SEER database study on extragonadal choriocarcinoma in males reported a median survival of 12 months and a 5-year CSS of 25% among 67 patients with mediastinal primary choriocarcinoma NOS or choriocarcinoma combined with other germ cell elements, which is the same to that obtained in our 87 patients of the same histologies 35. A small series of Korean patients from the Samsung Medical Center reported a median OS of 8 months for the group of 6 patients with primary mediastinal choriocarcinoma 36. Concerning mediastinal yolk sac tumors, the prognosis seems to be better than that of the rest of the NS tumors, as well as those obtained in our series.…”
Section: Discussionsupporting
confidence: 83%
“…35 A small series of Korean patients from the Samsung Medical Center reported a median OS of 8 months for the group of 6 patients with primary mediastinal choriocarcinoma. 36 Concerning mediastinal yolk sac tumors, the prognosis seems to be better than that of the rest of the NS tumors, as well as those obtained in our series. The 5-year CSS of 81 male patients with mediastinal yok sac tumors reported from a SEER database study (diagnosed between 2004 and 2016) was 56.5%, 37 whereas a small Chinese series with 15 mediastinal yolk sac tumors observed a 2-year OS of 73.3%.…”
Section: Discussionsupporting
confidence: 82%
“…Primary mediastinal choriocarcinoma is extremely rare (2), and is often misdiagnosed or delayed in treatment. Currently, there is no standardized treatment for primary mediastinal such as Pembrolizumab, might be a salvage treatment for chemotherapy-resistant male PCC patients (5). We present the following case in accordance with the CARE reporting checklist (available at https://tcr.amegroups.com/article/ view/10.21037/tcr-22-766/rc).…”
Section: Introductionmentioning
confidence: 96%
“…Programmed cell death 1 ligand 1 (PD-L1) is ubiquitously expressed in choriocarcinoma tumors ( 4 ), indicating programmed cell death 1 (PD-1) inhibitor, such as Pembrolizumab, might be a salvage treatment for chemotherapy-resistant male PCC patients ( 5 ). We present the following case in accordance with the CARE reporting checklist (available at https://tcr.amegroups.com/article/view/10.21037/tcr-22-766/rc ).…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxic chemotherapy regimens based on those used to treat female choriocarcinomas or male germ cell tumors are conventionally adopted for PPC treatment; however, these therapies have limited efficacy. Immune checkpoint inhibitors (ICIs) could potentially be used to treat chemotherapy-resistant choriocarcinoma, as they engender long-term survival benefits and durable responses against multiple tumor types ( 3 ).…”
Section: Introductionmentioning
confidence: 99%